Bilinguals vs. Multilinguals :the differences in short term memory and attention performances - Nurul Shuhadah, Muhamed. (Universiti Malaysia Sarawak, UNIMAS, 2006)
Generally, the focus of this research is to determine whether there exist differences in short term memory and attention performances between the bilinguals and multilinguals . Matter arises wit h the question of whether mastering more languages will burden the brain cognitive processing or vice versa. The experiment design is quasi - experiment since no control group was involved and the instrument used to measure short term memory and attention wa s using the Cognitive Psychology Laboratory on a CD (CogLab) . The Brown - Peterson test was used to measure the short term memory performance and the Stroop effect test was used to measure the attention performance. Sixteen (16) form four students from Sekol ah Menengah Jalan Batu Lintang and sixteen (16) students from University Malaysia Sarawak has been chosen as the participants in this study. No significant difference was found in short term memory performance between the bilinguals and multilinguals. Howe ver, there was a significant difference in attention performance between the bilinguals and multilinguals. The multilinguals scored better in the Stroop effect test compared to their bilinguals’ peers. This proves that actually mastering or learning more l anguages does not bring you harm, in fact it enhances the cognitive processes.